Cognitive function in SMA patients with 2 or 3 SMN2 copies treated with SMN-modifying or gene addition therapy during the first year of life - Steffens, Paula; Weiss, Deike; Perez, Anna; Appel, Manuel; Weber, Philipp; Weiss, Claudia; Stoltenburg, Corinna; Ehinger, Ute; von der Hagen, Maja; Schallner, Jens; Claussen, Birte; Lode, Ilka; et al. (European journal of paediatric neurology, 2024)
Background - Spinal muscular atrophy (SMA) is a neuromuscular disease, causing progressive muscle weakness due to loss of lower motoneurons. Since 2017, three therapies, two modifying gene transcription and one adding the defective gene, have been approved with comparable efficacy on motor outcome. Data on cognitive outcomes of treated SMA type 1 patients is limited. The aim of this study was to evaluate cognitive function in symptomatic and presymptomatic SMA type 1 patients with two or three SMN2 copies who received SMN-modifying or gene-addition therapy in the first year of life. - Methods - Cognitive testing was performed in 20 patients, including 19 symptomatic SMA type 1 patients with up to three SMN2 copies and 1 pre-symptomatically treated patient. Children were tested using Bayley Scales of Infant Development (BSID-III) at the age of 2 or 3 years or the Wechsler Preschool and Primary Scale of Intelligence (WPSII-IV) at the of age of 5 years. - Results - 11/20 patients showed subnormal cognitive development. Boys had significantly lower cognitive scores. Patients requiring assisted ventilation or feeding support were more likely to have cognitive deficits. Achieving more motor milestones was associated with a better cognitive outcome. - Conclusion - Treated patients with SMA type 1 have heterogeneous cognitive function with 55 % of patients showing deficits. Risk factors for cognitive impairment in our cohort were male gender and need for assisted ventilation or feeding support. Therefore, cognitive assessment should be included in the standard of care to allow early identification of deficits and potential therapeutic interventions.